Pengaruh Intellectual Capital dan Net Interest Margin Terhadap Kinerja Keuangan Sektor Perbankan Dimoderasi Pertumbuhan Dana Pihak Ketiga - Wulan Sari Ardiyanti; Basuki Toto Rahmanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine the effect of intellectual capital and net interest margin on financial performance moderated by the growth of third party funds. Intellectual capital is measured by the Value Added Intellectual Capital (VAICTM) method, net interest margin is measured by the ratio of interest income to earning assets, and financial performance is measured by Return on equity (ROE). Using the population of banking companies listed on the IDX in 2016-2020. The technique used in determining the sample is purposive sampling with a total of 200 observations at banking companies. The analytical technique used in this research is Moderate Regression Analysis (MRA). The hypothesis is accepted if the probability value is 0.05. The results of this study indicate that: (1) intellectual capital has no effect on financial performance, (2) net interest margin has no effect on financial performance, (3) growth of third party funds strengthens the influence of intellectual capital on financial performance, (4) growth of third party funds the third does not moderate the effect of net interest margin on financial performance.